Morbidity Profile of Pregnant Women Attending Antenatal Clinic in Nanyuki Teaching and Referral Hospital, Kenya - A Cross Sectional Study (P11-015-19). (13th June 2019) - Kiboi, Willy; Kimiywe, Judith; Chege, Peter
Abstract: Objectives: To determine the health morbidity profile of pregnant women attending antenatal clinic in Nanyuki Teaching and Referral hospital, Kenya. Methods: A cross-sectional study was conducted among pregnant women where data on maternal morbidity profile was collected. A total of 254 pregnant women attending antenatal clinic were recruited. Results: More than half (57.5%) of the women recruited in this study reported to be unwell in the immediate two weeks preceding the day of the interviews. The common diseases/disorders reported were heartburn (42.9%), anemia (16.9%) anorexia (15.4%), vomiting (14.2%) and constipation (11.4%) with most of them having a duration of more than 7 days. Other morbidities such as fever, abdominal pain, upper respiratory infection, diarhoea and headache were also reported. Further, out of all those who reported being sick, only 40.4% who sought medical attention. Conclusions: Morbidity among the pregnant women was notably high. Public health awareness campaigns among pregnant women on prevention, early identification and timely treatment of diseases/disorders during pregnancy should be up-scaled. Funding Sources: None.